The research reproducibility crisis and economics of science - Maniadis, Zacharias; Tufano, Fabio (Wiley, 2017)
We provide a brief summary of two areas where cross-fertilization across economics and other disciplines is likely to have far-reaching benefits. The increasing concern about research reproducibility entails that economic design has much to contribute to the discussion of possible reforms in science, while the empirical discipline of meta-research can inform practices to assess the validity of the economics literature. A mutual investment in investigating possible synergies may be costly but could benefit the scientific endeavour as a whole.